A New Early Bronze Age House-Site under a Barrow at Hyllerup, Western Zealand - Pedersen, Jens-Aage (Journal of Danish Archaeology, 1986)
A New Early Bronze Age House-Site under a Barrow at Hyllerup, Western Zealand